2013
DOI: 10.1016/j.jacc.2013.03.088
|View full text |Cite|
|
Sign up to set email alerts
|

Computed Tomography Angiography and Myocardial Computed Tomography Perfusion in Patients With Coronary Stents

Abstract: Combined coronary CTA and myocardial CTP improves diagnosis of CAD and in-stent restenosis in patients with stents compared with CTA alone. (Coronary Artery Stent Evaluation With 320-Slice Computed Tomography-The CArS 320 Study [CARS-320]; NCT00967876).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 32 publications
4
52
1
Order By: Relevance
“…Our finding explains the extremely low PPV of CTP for the detection of in-stent restenosis as reported by Rief et al 39 For CTP to be truly useful in the evaluation of in-stent restenosis, differentiation between ischemia and infarction is necessary. The comprehensive CT study protocol in this study can provide discrimination of myocardial ischemia and infarction.…”
Section: Discussionsupporting
confidence: 67%
“…Our finding explains the extremely low PPV of CTP for the detection of in-stent restenosis as reported by Rief et al 39 For CTP to be truly useful in the evaluation of in-stent restenosis, differentiation between ischemia and infarction is necessary. The comprehensive CT study protocol in this study can provide discrimination of myocardial ischemia and infarction.…”
Section: Discussionsupporting
confidence: 67%
“…In this regard, Rief et al demonstrated in 92 patients that static CTP significantly improved the detection of instent restenosis (area under the curve from 0.69 to 0.92; P<0.0001) by reducing the number of non-diagnostic CTA examinations (62).…”
Section: Clinical Evidencementioning
confidence: 99%
“…[92][93][94] CT perfusion may improve the overall diagnostic accuracy of cardiac CT, particularly in the interpretation of intermediate (30-70%) stenosis, 95 in the evaluation of stent patency, 96 and of diffuse atherosclerotic involvement with densely calcified plaques 97 ( Figure 5). …”
Section: Plaque Features Associated With Vulnerabilitymentioning
confidence: 99%